Regulating Catalytic Properties and Thermal Stability of Pt and PtCo Intermetallic Fuel-Cell Catalysts via Strong Coupling Effects between Single-Metal Site-Rich Carbon and Pt - Zeng, Yachao; Liang, Jiashun; Li, Chenzhao; Qiao, Zhi; Li, Boyang; Hwang, Sooyeon; Kariuki, Nancy N.; Chang, Chun-Wai; Wang, Maoyu; Lyons, Mason; Lee, Sungsik; Feng, Zhenxing; et al. (Journal of the American Chemical Society, 2023)
Developing low platinum-group-metal (PGM) catalysts for the oxygen reduction reaction (ORR) in proton-exchange membrane fuel cells (PEMFCs) for heavy-duty vehicles (HDVs) remains a great challenge due to the highly demanded power density and long-term durability. This work explores the possible synergistic effect between single Mn site-rich carbon (MnSA-NC) and Pt nanoparticles, aiming to improve intrinsic activity and stability of PGM catalysts. Density functional theory (DFT) calculations predicted a strong coupling effect between Pt and MnN4 sites in the carbon support, strengthening their interactions to immobilize Pt nanoparticles during the ORR. The adjacent MnN4 sites weaken oxygen adsorption at Pt to enhance intrinsic activity. Well-dispersed Pt (2.1 nm) and ordered L12-Pt3Co nanoparticles (3.3 nm) were retained on the MnSA-NC support after indispensable high-temperature annealing up to 800 °C, suggesting enhanced thermal stability. Both PGM catalysts were thoroughly studied in membrane electrode assemblies (MEAs), showing compelling performance and durability. The Pt@MnSA-NC catalyst achieved a mass activity (MA) of 0.63 A mgPt –1 at 0.9 V iR‑free and maintained 78% of its initial performance after a 30,000-cycle accelerated stress test (AST). The L12-Pt3Co@MnSA-NC catalyst accomplished a much higher MA of 0.91 A mgPt –1 and a current density of 1.63 A cm–2 at 0.7 V under traditional light-duty vehicle (LDV) H2–air conditions (150 kPaabs and 0.10 mgPt cm–2). Furthermore, the same catalyst in an HDV MEA (250 kPaabs and 0.20 mgPt cm–2) delivered 1.75 A cm–2 at 0.7 V, only losing 18% performance after 90,000 cycles of the AST, demonstrating great potential to meet the DOE targets.